2006
DOI: 10.1097/01.aids.0000210615.83330.b2
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and HIV in Tanzanian couples: both mobile persons and their partners show increased risk

Abstract: More sexual risk behavior and an increased risk of HIV infection were seen not only in mobile persons, but also in partners staying behind. Interventions aiming at reducing risk behavior due to mobility should therefore include partners staying behind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 13 publications
7
88
0
Order By: Relevance
“…We recommend that approaches dealing with the health of commercial sex workers should be expanded to include protection of their human rights, access to health care without discrimination and attention to psychosocial health issues, such as addiction and violence, because they have specific needs as sex workers in addition to general reproductive and sexual health needs (Chacham et al, 2007). The social impact of limited resources and adverse social conditions (Kishamawe et al, 2005;Dworkin and Ehrhardt, 2007), especially among commercial sex workers in Maputo, Mozambique, should be addressed to allow them to achieve a stable healthy life. We believe the results regarding the skills of commercial sex workers will be useful to develop strategies and methods of health education to improve the condition of health and promote healthy living in this population living under fragile conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that approaches dealing with the health of commercial sex workers should be expanded to include protection of their human rights, access to health care without discrimination and attention to psychosocial health issues, such as addiction and violence, because they have specific needs as sex workers in addition to general reproductive and sexual health needs (Chacham et al, 2007). The social impact of limited resources and adverse social conditions (Kishamawe et al, 2005;Dworkin and Ehrhardt, 2007), especially among commercial sex workers in Maputo, Mozambique, should be addressed to allow them to achieve a stable healthy life. We believe the results regarding the skills of commercial sex workers will be useful to develop strategies and methods of health education to improve the condition of health and promote healthy living in this population living under fragile conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ward includes an urban centre situated around the main road, a peri-urban area surrounding the urban centre, with the remainder of the ward classified as rural (Boerma, Urassa, Senkoro, Klokke, & Ngweshemi, 1999), and is increasingly under the sphere of influence of Mwanza city. The study site was chosen as it was the site of two previous statistical studies on mobility and HIV (Kishamawe et al, 2006;Vissers et al, 2008) that came to different conclusions (Deane et., al 2010), and also reported high levels of mobility, with 60% of men and 43% of women classified as mobile in the study by Kishamawe et al (2006). Sexual behaviours reported in these studies suggested that approximately 30% of the male population had a casual partner, and that around 45% of men had two or more sex partners (Kishamawe et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The study site was chosen as it was the site of two previous statistical studies on mobility and HIV (Kishamawe et al, 2006;Vissers et al, 2008) that came to different conclusions (Deane et., al 2010), and also reported high levels of mobility, with 60% of men and 43% of women classified as mobile in the study by Kishamawe et al (2006). Sexual behaviours reported in these studies suggested that approximately 30% of the male population had a casual partner, and that around 45% of men had two or more sex partners (Kishamawe et al 2006). Vissers et al (2008) report that in their sample, 67.8% of coresidents and 86.6% of couples living apart had unprotected sex at their last extramarital sex act.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations